ANALISIS PENGARUH PROVIDE INFORMATION, TECHNICAL SKILLS, DAN SUBJECTIVE NORMS TERHADAP PURCHASE INTENTION PADA SECONDARY SNEAKER MARKET DENGAN ATTITUDE TOWARDS RESALE RETAILERS SEBAGAI VARIABEL MEDIASI - Aida Yunani; Willy Arafah (STMIK Widuri Jakarta, 2026)
This study examines the effects of provide information, technical skills, and subjective norms on purchase intention in the secondary sneaker market with attitude towards resale retailers as a mediating variable. A quantitative survey was conducted with 166 respondents from Generation Z and millennials in Jakarta. Data were analyzed using Structural Equation Modeling (SEM). The results indicate that provide information has a positive and significant effect on attitude towards resale retailers, and subjective norms positively affect purchase intention. However, technical skills and attitude towards resale retailers do not significantly affect purchase intention. These findings highlight the importance of information transparency and social influence in shaping purchase intention in the secondary sneaker market.